Modelling and simulation of B3G multi-service traffic in the presence of mobility - Juárez, Jesús M. (2009)
A multi-service traffic model is proposed, and its validation is achieved by using event-based simulation results which consider the burstiness of traffic. By considering the deployment scenarios and tele-traffic parameters from the Vehicular scenario of IST-SEACORN, a simulator was produced to extract conclusions about blocking and handover failure probabilities. Simulations, were performed for different cases, from single- to multi-service situations, and from absence to presence of mobility. Besides results for the quality of service in the air interface, including blocking and handover failure probabilities for several types of traffic, the simulator allows for extracting conclusions about the validation of the Bernoulli/Poisson/Pascal model for the computation of the on/off blocking probability, the ratio between the number of session rejected at the beginning of an on period and the total number of bursts generated during a session. In the single-service case, the theoretical and the experimental values of on/off blocking probability are close to each other. An almost perfect concordance between theoretical and simulation values is verified when the average sojourn time in cells is equal to the average holding time. In the multi-service case, although the results are not exactly coincident a coherent behaviour is achieved for an average traffic per user up to 0.06 Erl.